Analisis Distribusi Tegangan Pada Kepala Baut Dengan Variasi Filet Menggunakan Metode Fotoelastisitas - Sukarnoto, Tono; Soeharsono, Soeharsono (MESIN, 2007)
Stress Distribution Analysis on Bolt Head with Various Fillets Using PhotoelasticityMethod. A geometry modification can be use to reduce stress concentration. This research isinvestigating the influence offillet radius in the head ofbolt. Different than most commonbolt, thefillet ismade at the bottom surface of head around its neck. To show the stress distribution we use classicalexperimental mechanics method, photo elasticity. Loading comesfrom a lead screw and measured by aload cell connected to a computer data logger. As the result, a 5 mm fillet radius may reduce maximumshear stress up to 35%than nofillet radius, so its effective to minimize stress concentration in head bolt.